음압격리병실으로의 전환을 고려한 일반병동의 건축계획에 대한 연구 - 권순정; 김지윤 (의료·복지 건축, 2024)
Purpose: As infectious diseases spread, hospitals have converted general wards into negative pressure isolation wards through remodeling. During the conversion process, there were limitations in converting the existing ward into an effective isolation ward due to its existing structure and mechanical system. To minimize these problems, this study proposes some general ward planning methods taking into account effective conversion to an infectious disease ward. Methods: Seven rapid conversion isolation wards have been analyzed in order to check their appropriateness as a negative pressured isolation unit. Then, general ward design planning methods that can minimize problems in rapidly converted negative pressured wards have been derived. Results: If general wards can be efficiently converted into negative pressure isolation wards, many isolation facilities can be secured effectively in a short period of time during a pandemic.
Keywords: Infectious Disease; Negative Pressured Isolation Unit; Remodeling; Pandemic; 감염병; 음압격리병실; 리모델링; 팬데믹